Psychologically accessing ownership : how does individual psychological ownership (IPO) affect peer-to-peer access-based consumption (P2P-ABC)? - Teixeira, Otávio Ferreira Borges (2021)
Tese (doutorado) — Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade e Gestão Pública, Programa de Pós-Graduação em Administração, 2021.